“La psicología organizacional en la evaluación del desempeño de los trabajadores de la empresa máquinas para el agro Maqgro Cia.Ltda” - Alvarado Sánchez, Carla Valentina (2025)
The present study, entitled “Organizational Psychology in the Performance Evaluation of Workers at MAQUINAS PARA EL AGRO MAQGRO CIA. LTDA.”, aims to determine the influence of psychological factors on employee performance. The research analyzes key organizational psychology elements such as motivation, interpersonal relationships, recognition, organizational climate, and communication. A mixed-methods approach was applied, consisting of structured surveys conducted with the company's seven employees and a semi-structured interview with the general manager. The study followed a non-experimental, cross-sectional, and descriptive design, enabling the collection of real and context-based data without altering work conditions. The results revealed significant weaknesses in talent management practices. The absence of a formal performance evaluation system, insufficient training programs, and a lack of psychological support strategies were among the key findings. Employees expressed dissatisfaction with the lack of recognition and communication, although some appreciated the collaborative environment. Based on these findings, several strategies are proposed to improve human talent management through organizational psychology. These include hiring an organizational psychologist, developing a comprehensive performance evaluation system, enhancing communication channels, and fostering emotional well-being.